121 Post-exertional hypotension and collapse in marathon runners; the role of muscle mass, histamine and mast cell tryptase. (17th July 2020) - Parsons, Iain; Stacey, Michael; Hill, Neil; Patten, Alex; Faconti, Luca; Farukh, Bushra; McNally, Ryan; Chowienczyk, Phil; Gall, Nick; Woods, David
Abstract : Introduction: Post-exertional hypotension is the sustained reduction in arterial blood pressure (BP) following exercise which, if severe enough, can lead to syncope and exercise-induced collapse particularly following the cessation of exercise. Elevations in skeletal muscle blood flow, coupled with an inactive muscle pump lead to marked reductions in venous return which is exacerbated in hot environments. Exercise also generates a sustained post-exertional vasodilation within the vascular beds of previously active skeletal muscle driven through activation of histamine receptors. Previous studies have demonstrated that the use of histamine receptor antagonists blocks 80% of post-exercise vasodilation. Several possible mechanisms may increase intramuscular histamine during recovery from exercise. Mast cells located within the connective tissue layer surrounding skeletal muscle fascicles or near blood vessels may degranulate, releasing histamine locally in response to exercise related factors. Histamine can also be formed de novo without storage in mast cells through histidine decarboxylase. Previous studies have found no change in circulating plasma histamine concentrations however. Method: Twenty-four runners were recruited as controls prior to completing a standard marathon. A resting transthoracic echocardiogram (TTE) was performed at baseline and immediately following completion of the marathon in conjunction with bioelectrical impedance, blood pressure (BP), heart rate (HR), plasma histamine and mast cell tryptase levels. Eight runners who collapsed during, or following, the marathon were recruited with blood pressure, heart rate, plasma mast cell tryptase and plasma histamine measured as soon as possible following collapse. Results: Control participants (n=24) had a significantly increased plasma mast cell tryptase (pre; 806±386ng/L, post; 1179±422ng/L, p=0.012) post marathon in comparison to baseline with a significantly decreased IVCd (p=0.0004), stroke volume (p <0.0001), body mass (p <0.0001), fat mass (p=0.006), muscle mass (p=0.044) and mean arterial pressure (MAP) (p=0.0052). Control participants' systolic BP (r= -0.440, p=0.046), diastolic BP (r= -0.60, p=0.0043) and MAP (r=-0.60, p=0.0039) were all significantly negatively correlated with their muscle mass post marathon. In comparing collapse and control participants, collapsed participants had a significantly higher histamine (9.6±16.6μg/L) compared to control pre-marathon measures (0.45± μg/L, p=0.016). Compared to control post-marathon measures the collapsed groups had a significantly lower MAP (collapse; 68.2±7.7mmHg, control 76.64±7.92, p=0.031) and a significantly higher mast cell tryptase (collapse; 1769±244ng/L, control; 1179±422ng/L, p=0.001). Conclusion: These data confirm that following a marathon there is a significant rise in plasma mast cell tryptase. The degree of post exertional hypotension is significantly correlated with participants muscle mass. Collapsed participants, whom have a significantly lower MAP than post-marathon controls, have a significantly higher mast cell tryptase. These findings support the hypothesis that skeletal muscle vasodilation by histamine release, probably through mast cell degranulation, is contributory to post-exertional hypotension. Conflict of Interest: None